اقتراح منهجية لاختيار الطريقة التجريبية الأنسب لتصحيح المرئيات الفضائية - ديب, فايز; الخليل, عمر; ديوب, وائل; علي, أحمد (Latakia University Journal -Engineering Sciences Series, 2018)
In recent years، high resolution satellite images (HRSI) become one of the basic source of information required for producing and updating big scale maps. The accuracy of extracted data from these images depends on accuracy of mathematical models for the satellite sensor that describe the relationship between image and objects spaces. But، in most cases, there is no satellite orbit information for these new sensors. In this case, we apply empirical methods based on control points to define this relationship (e.g. geometric correction of images) and to transform image to source of spatial information. In this research, we experimented some of these empirical methods to achieve the geometric correction of a High Resolution Satellite Images (HRSI) covered a part of Lattakia state (a QUICKBIRD image white a spatial resolution equal to 0.6 m). When applying these methods, the coordinates of control points were measured by GPS, in WGS-84, using static method. These coordinates were then transformed into the Syrian local coordinate system. The results of the experiment show that the second and third order polynomials, are appropriate to correct satellite images that cover limited areas. In the case of planimetric areas, we found that the projective transformation is very effective; and the rubber sheet is the most appropriate when a large amount of control points, covering the whole imaged scene, is available. في السنوات الأخيرة، صارت المرئيات الفضائية ذات دقة التمييز المكانية العالية مصدراً أساسياً للمعلومات اللازمة من أجل صناعة الخرائط ذات المقاييس الكبيرة أو تحديثها. هذا، وتعتمد دقة البيانات المكانية المقتطعة من هذه المرئيات على دقة النماذج الرياضية للمستشعرات والتي تصف العلاقة بين حيّز المرئية وحيّز العنصر. ولكن في أغلب الحالات، لا تتوفر معلومات حول مدار التابع الصنعي الحامل لهذه المستشعرات الجديدة. وهنا، يتم تطبيق طرائق تجريبية قائمة على استخدام نقاط الضبط في تعريف هذه العلاقة (أو ما يسمى بالتصحيح الهندسي للمرئيات) وذلك لتحويل المرئيات إلى مصدر للبيانات المكانية. يهدف البحث بشكل اساسي الى وضع منهجية علمية لاختيار أفضل طريقة تجريبية لتصحيح مرئية فضائية ما. تم في هذا البحث اختبار بعض الطرائق التجريبية في إنجاز التصحيح الهندسي لمرئية فضائية ذات دقة تمييز عالية تغطي منطقة من محافظة اللاذقية (هذه المرئية من النوع QUICKBIRD والتي دقة تمييزها المكانية تساوي 0.6 m). حيث تم قياس إحداثيات نقاط الضبط في الجملة العالمية WGS-84 باستخدام أجهزة الاستقبال GPS بالطريقة الساكنة وتحويلها الى الجملة المحلية في سوريا. وجدنا أن كثيرات الحدود من الدرجتين الثانية والثالثة هي الانسب لمسألة التصحيح الهندسي للصور الفضائية التي تغطي مشاهد محدودة الاتساع. في حين أن التحويل الإسقاطي يكون فعالاً في حالة المشاهد المستوية والشد المرن يكون أكثر الطرق فعاليةً في حال توفر عدد كبير من نقاط الضبط التي تغطي كامل المشهد المصور.